Research and Application of a Fast Recovery Strategy for Complex Structure Networks Based on Sorting Multi-objective. Issue 1 (1st February 2022) - Dang, Yijie; He, Yunrui; Zhang, Shulin; Chen, Liang; Liu, Guangxu; Zhang, Xiangyi; Bai, Shuo
Abstract: With the development of information technology, the scale of data centers and the number of equipment are experiencing explosive growth, and the network structure of data centers has also continued to develop and mature. The more complex network structure increases the possibility of network failures and the difficulty of operation and maintenance. When an unpredictable failure occurs in the network, in order to quickly recover the network, a multi-objective complex structure network rapid recovery strategy is proposed. Under the goal of the shortest failure time, minimum reduction of safety protection, and maximum possible restoration of the original method, a restoration plan is given.